The Meaning of Distraction: How Metacognitive Inferences from Distraction during Multitasking Affect Brand Evaluations - Zane, Daniel M; Smith, Robert W; Reczek, Rebecca Walker (Journal of Consumer Research, 2020)
AbstractConsumers often encounter advertisements in the background while primarily focused on other stimuli (e.g., while multitasking). Consumers’ perceived level of distraction by these background ads serves as a metacognitive cue from which inferences are drawn. When consumers perceive themselves to be relatively distracted by a background advertisement, they draw on an underlying lay theory that distraction implies interest in the contents of the distracting stimulus to make the metacognitive inference that they have positive evaluations of the advertised brand. Across five studies, we provide evidence for this proposed metacognitive inferential process by demonstrating that perceived distraction does not enhance brand evaluations when the distraction = interest lay theory is not perceived to be (1) diagnostic or (2) applicable to the current context (e.g., when consumers have little interest in the product category being advertised). Thus, this research introduces distraction as a new metacognitive experience from which consumers draw inferences and offers important insights into when and how background ads shape brand evaluations.